THE STUDENT’S ERRORS INVESTIGATION IN USING PUNCTUATION, CAPITALIZATION AND SPELLING IN WRITING BUSINESS LETTER - Fanalisa Elfa; Muhammad Sabri; Loly Novita; Aswandi Aswandi (Politeknik Negeri Bengkalis, 2022)
This study aims to investigate the errors committed by students in using punctuation, capitalization and spelling in writing business letter. This is descriptive study. The sample of this study was the students of English for Professional Business and Communication Program Academic Year 2021/2022. The finding of the research showed that the common errors committed by students in writing business letter from the highest to the lowest occurrence were spelling, punctuation and capitalization. The errors occur because of omission, addition, misformation and misordering.Â